Early changes of bone metabolites and lymphocyte subsets may participate in osteoporosis onset: a preliminary study of a postmenopausal osteoporosis mouse model - Wang, Sizhu; Qiu, Yuyou; Tang, Cuisong; Tang, Huan; Liu, Jinchuan; Chen, Jieying; Zhang, Lin; Tang, Guangyu (Frontiers in Endocrinology, 2024)
Purpose Metabolic and immune changes in the early stages of osteoporosis are not well understood. This study aimed to explore the changes in bone metabolites and bone marrow lymphocyte subsets and their relationship during the osteoporosis onset. Methods We established OVX and Sham mice models. After 5, 15 and 40 days, 5 mice in each group were sacrificed. Humeri were analyzed by microCT. The bone marrow cells of left femur and tibia were collected for flow cytometry analysis. Right femur and tibia were analyzed by LC-MS/MS for metabolomics analysis. Results Bone microarchitecture was significantly deteriorated 15 days after OVX surgery. Analysis of bone metabolomics showed that obvious metabolites changes had happened since 5 days after surgery. Lipid metabolism was significant at the early stage of the osteoporosis. The proportion of immature B cells was increased while the proportion of mature B cells was decreased in the OVX group. Metabolites were significantly correlated with the proportion of lymphocyte subsets at the early stage of the osteoporosis. Conclusions Lipid metabolism was significant at the early stage of the osteoporosis. Bone metabolites may influence bone formation by interfering with bone marrow lymphocyte subsets.